The Role of Islamic Law in Increasing Public Understanding of Islamic Values in Sharia Banks - munawaroh; Nurhayati; Sri Sudiarti (Faculty of Law, Universitas Pekalongan, 2024)
Understanding Islamic law is something that is often seen in implementing an existing contract in Islamic banks or Islamic financial institutions. But currently, many people do not understand this matter. Therefore, from these problems, the researcher wanted to test the variables of Islamic Law Understanding (X1), Islamic Economic Literacy (X2) and Religisutas (X3) on the Understanding of Islamic Values in Sharia Banks (Y). This study uses a quantitative approach with the SmartPLS analysis tool. The results of the study found that there was an influence of the variable Literacy of Islamic law understanding (X1) had a significant effect on the understanding of Islamic Values in Sharia Banks (Y) by 44.10%. Then Islamic economic literacy (X2) has a significant effect on the Understanding of Islamic Values in Sharia Banks (Y) by 27.47%, and lastly there is no influence of Religiosity (X3) on the Understanding of Islamic Values in Sharia Banks (Y).